The Influence of Organizational Memory, Knowledge Recovery, Knowledge Visualization and Knowledge Transfer on Improving the Career of Lecturer at Private Universities in The Region of West Java and Banten - Sunarsi, Denok; Affandi, Azhar; Narimawati, Umi; Priadana, Sidik; Djulius, Horas; Sudirman, Imam (Universitas Dharma Wacana, 2023)
The research aims to determine the influence of organizational memory, knowledge recovery, knowledge visualization and knowledge transfer on improving the careers of lecturers at private universities in the West Java and Banten regions. This research uses a type of quantitative research with a survey approach with the method used is purposive sampling, with a sample of 211 lecturers. The data analysis technique for this research uses PLS software version 3.0 (Partial Least Square) with the research results showing that (1) organizational memory has a significant negative effect on improving lecturers' careers with a t statistic value of 2,000 > t table 1.652 and a P-value of 0.046 < 0.05, with a relationship of 5.9% (2) knowledge recovery has a positive and significant effect on improving lecturers' careers with a t statistical value of 5.113 > t table 1.652 and a P-value of 0.000 < 0.05, and a relationship value of 43.8 % (3) knowledge visualization has a positive and significant effect on improving Dodsen's career with a t statistical value of 6.236 > t table 1.652 and a P-value of 0.000 < 0.05, with a relationship value of 49.9% (4) Knowledge transfer has a significant positive effect on lecturer career improvement with a t statistic value of 6.236 > t table 1.652 and a P-Value of 0.026 <0.005, and with a relationship value of 12.6%.